Letters of delegates to Congress, 1774-1789 - Smith, Paul Hubert, 1931-; Gawalt, Gerard W.; Plakas, Rosemary Fry; Sheridan, Eugene R.; Gephart, Ronald M. (LLMC-digital (Series), 1976)
The twenty-six volumes of the Letters of Delegates to Congress, 1774-1789 aims to make available all the documents written by delegates that bear directly upon their work during their years of actual service in the First and Second Continental Congresses, 1774-1789. [Edited by Paul H. Smith]